A comparison of native and non-native EFL teachers based on learner performance and stakeholders’ perceptions / Hossein Ali Majlesifard - Hossein, Ali Majlesifard (2012)
Controversies on the native and non-native English teacher dichotomy have been historically a matter of concern according to many pioneering scholars of the field. Although a great deal of research in the field of teaching English as a foreign language has compared native and non-native speaking English teachers (henceforth N/NNSETs), to the best of the researcher’s knowledge no attempt has been made so far to examine the outcome of the performance of these two teacher types in the Iranian EFL context. Be that as it may, this study focused on EFL learners, EFL teachers, and policy makers in Iran. The aim of the study was to explore the performance and the perceptions of EFL learners taught by N/NNSETs. The study also investigated self-perceptions of native and non-native EFL teachers about their strengths and weaknesses as well as the attitudes of administrators towards these two groups of teachers (N/ NNSETs). Qualitative and quantitative data were collected to test the following two main research hypotheses: 1) Teachers’ nationality (N or NN) has no differential effect on the development of oral proficiency of Iranian EFL learners; 2) Learners, teachers, and private language institute administrators perceive no differences between N and NNSETs. A mixed method research design including an experimental phase and a survey phase was employed to examine a) oral performance of the learners taught by N/NNSETs, b) learners’ perceptions of N/NNSETs, c) teachers’ self-perceptions regarding their strengths and weaknesses, and d) perspectives of private language institutes administrators of N/NNSETs. In the experimental phase, 3 native and 3 non-native speaking English teachers taught 90 females aged 11-13 (all of whom were beginning EFL learners) in six groups of 15 in an Iranian provincial language institute. The treatment was carried out for three 100-minute sessions per week totaling 50 sessions. At the end of the treatment, a semi-direct oral test was administered to compare gains in learners’ oral proficiency. Another measure of the fluency of the two iv groups of the EFL learners taught by NSETs and NNSETs was also considered by enumerating the number of mid- clause pauses made by the participants when recounting a simple narrative based on a series of picture prompts. In the survey phase, three questionnaires for students (n=213), teachers (n=36) and administrators (n=21) were used to collect data on perceptions of N and NNSETs. The data from both phases were carefully recorded in SPSS files and analyzed using frequencies, descriptive statistics, inferential tests like ANOVAs and Student T-Tests, and qualitative techniques. The analyses indicated that despite the outperformance of those taught by NSETs in the oral proficiency test, the learners were not as concerned by the nationality of their teachers as much as their qualification. It was the perceived poor qualification of native Iranian EFL teachers that was a matter of concern to the learners. Surveys of teachers’ self perceptions showed lack of self confidence and poor pedagogical and linguistic competence on the part of NNSETs. They perceived themselves as just grammar experts. Private language institutes’ administrators laid emphasis on cooperation of the two groups of the teachers in the belief that the previous learning experience of Iranian English teachers can compensate for their weaknesses in linguistic and communicative performance. The findings imply that concrete steps need to be taken by the authorities for teaching, training, and hiring qualified English teachers irrespective of their native or nonnative origin.